IMPLEMENTASI REFERENSI RATE OF RETURN TERHADAP REPUTASI PEMBIAYAAN PERBANKAN SYARIAH - Anggraini, Erike (ASAS, 2013)
Abstrak: Rate of return-reference becomes investment guidelines for Islamic banking financing. This reference drives the implementation of profit-loss sharing in real sector as typical of Islamic principle. It should refers to general investment guidelines also added by mashlahah variable, so that it will not only rely the benefit for some groups but also bring social welfare for wider community. Therefore, it can manage sharia-bank’s reputation as financial institution which is more than just a bank. Keyword : Rate of Return, Pembiayaan, Perbankan Syari’ah